Do official multidimensional poverty measures in Latin America reflect the priorities of people living in poverty? - Clausen, Jhonatan; Vargas, Silvana; Barrantes, Nicolás (Ensayos de Política Económica, 2019)
This article analyses the design process of official multidimensional poverty measures in Colombia, Chile, El Salvador and Mexico, and discusses the extent to which such processes have been able to reflect the priorities of people living in poverty. We argue that although these countries have faced limitations in conducting a ”pure participatory-driven” strategy, they have advanced towards measuring poverty in a way that better reflects what disadvantaged people consider to be an impoverished life. We propose guidelines to continue improving the design of official multidimensional poverty measures and make them more open to information on what people value and more sensitive to public reasoning.